Analisis Pendampingan Orang Tua Didalam Kelas terhadap Perkembangan Emosional Anak Usia Dini - Siti Meilan Pratiwi; Farida Lomuli; Tanti Tanti; Maya Sara; Nadia Alamri (ICHIGO : Jurnal Bahasa, Sastra, Pendidikan, dan Budaya Jepang, 2024)
The intensity of parental learning assistance refers to how deeply parents are involved in accompanying the child's learning process according to their age, so that all aspects of child development can develop optimally. This study aims to analyze the influence of parental assistance in the classroom on early childhood emotional development. Early childhood, namely children aged 0–6 years, is in a very rapid period of development, which is often referred to as the golden age. This period illustrates how quickly early childhood develops in all aspects of life. In this phase, children need consistent guidance, a stable emotional presence, and positive stimulation from their immediate environment, especially parents. Assistance that is carried out intensely and according to the needs of children is believed to be able to form a sense of security, improve emotional regulation skills, and encourage children to express their feelings in a healthy way. In addition, parental involvement in the classroom not only supports the formal learning process, but also strengthens parent-child relationships so as to increase children's confidence and social readiness in interacting with peers. This approach is expected to provide a strong emotional foundation for the child's development at the next stage.